2016
DOI: 10.3354/meps11558
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient supply controls picoplankton community structure during three contrasting seasons in the northwestern Mediterranean Sea

Abstract: Picoplankton (ca. < 2 µm in diameter) are the most abundant organisms in the ocean. They often dominate planktonic biomass and primary production (Chis holm 1992, Marañón 2015, and could represent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 73 publications
5
30
1
Order By: Relevance
“…In theory, deeper samples should experience higher nutrient supply. Mouriño-Carballido et al (2016) found a negative relationship between nutrient supply (deeper samples) and cell size of Prochlorococcus, Synechococcus and small picoeukaryotes, a result consistent with ours in the case of the picoeukaryotes but not for the prokaryotes. Finally, Falkowski and Owens (1980) reported a clear decrease in size with light limitation in two large species of phytoplankton.…”
Section: Discussionsupporting
confidence: 91%
“…In theory, deeper samples should experience higher nutrient supply. Mouriño-Carballido et al (2016) found a negative relationship between nutrient supply (deeper samples) and cell size of Prochlorococcus, Synechococcus and small picoeukaryotes, a result consistent with ours in the case of the picoeukaryotes but not for the prokaryotes. Finally, Falkowski and Owens (1980) reported a clear decrease in size with light limitation in two large species of phytoplankton.…”
Section: Discussionsupporting
confidence: 91%
“…This prediction could be in conflict with observations of decline in ocean productivity governed by increased water column-stratification (Bouman et al, 2011). A shift in the community toward increasing dominance of picoeukaryotes will require additional nutrients inputs, as picoeukaryotes abundance in this study were positively related to nutrients concentration, as described for the Pacific Ocean (Blanchot et al, 2001) and to oceanic nutrient supply (Mouriño-Carballido et al, 2016). Our prediction of increasing dominance of Prochlorococcus is in agreement with models based on increased thermal stratification in the oligotrophic ocean, forecasting a decrease in total biomass and mean cell phytoplankton size (Acevedo-Trejos et al, 2014).…”
Section: Discussioncontrasting
confidence: 79%
“…This new finding might be associated with the DIN concentrations measured during this study (Figure ) being less than those obtained during the autumn cruises performed in 2005 by Qiu et al (). Mourio‐Carballido et al () reported that the highest abundances Synechococcus (the PE‐rich group) were seen at intermediate levels of nitrate supply, and small picoeukaryotic groups increased their abundance under high‐nutrient supply, in the northwestern Mediterranean Sea. The work by Pinckney et al () also supports the view that phytoplankton blooms result from nutrient inputs in conjunction with increased freshwater in the Neuse River Estuary.…”
Section: Discussionmentioning
confidence: 99%